Monetary policy and bank profitability in a low interest rate environment - Carlo Altavilla; Miguel Boucinha; José-Luis Peydró (European Central Bank (ECB), 2017)
We analyse the impact of standard and non-standard monetary policy measures on bank profitability. For empirical identification, the analysis focuses on the euro area, thereby exploiting substantial bank and country heterogeneity within a monetary union where the central bank has implemented a broad range of unconventional policies, including quantitative easing and negative interest rates. We use both proprietary and commercial data on individual bank balance sheets and financial market prices. Our results show that monetary policy easing - a decrease in short-term interest rates and/or a flattening of the yield curve - is not associated with lower bank profits once we control for the endogeneity of the policy measures to expected macroeconomic and financial conditions. Importantly, our analysis indicates that the main components of bank profitability are asymmetrically affected by accommodative monetary conditions, with a positive impact on loan loss provisions and non-interest income largely offsetting the negative one on net interest income. We also find that a protracted period of low interest rates might have a negative effect on profits that, however, only materialises after a long period of time and tends to be counterbalanced by improved macroeconomic conditions. In addition, while more operationally efficient banks benefit more from monetary policy easing, banks engaging more extensively in maturity transformation experience a higher increase in profitability after a steepening of the yield curve. Finally, we assess the impact of unconventional monetary policies on market-based measures of expected bank profitability and credit risk, by employing an event study analysis using high frequency data, and find that accommodative monetary policies tend to increase bank stock returns and reduce credit risk.
Keywords: E52; E43; G01; G21; G28; 330; bank profitability; monetary policy; lower bound; quantitative easing; negative rates